High-resolution imaging of organic and inorganic nanoparticles at nanometre-scale resolution by X-ray ensemble diffraction microscopy - Ning-Jung Chen; Chia-Hui Yeh; Huai-Yu Cao; Nai-Chi Chen; Chun-Jung Chen; Chun-Yu Chen; Yi-Wei Tsai; Jhih-Min Lin; Yu-Shan Huang; Chien-Nan Hsiao; Chien-Chun Chen (Journal of Synchrotron Radiation)
Coherent diffraction microscopy (CDM) is a robust direct imaging method due to its unique 2D/3D phase retrieval capacity. Nonetheless, its resolution faces limitations due to a diminished signal-to-noise ratio (SNR) in high-frequency regions. Addressing this challenge, X-ray ensemble diffraction microscopy (XEDM) emerges as a viable solution, ensuring an adequate SNR in high-frequency regions and effectively surmounting resolution constraints. In this article, two experiments were conducted to underscore XEDM's superior spatial resolution capabilities. These experiments employed 55 nm-sized silicon–gold nanoparticles (NPs) and 19 nm-sized nodavirus-like particles (NV-LPs) on the coherent X-ray scattering beamline of the Taiwan Photon Source. The core–shell density distribution of the silicon–gold NPs was successfully obtained with a radial resolution of 3.4 nm per pixel, while NV-LPs in solution were reconstructed at a radial resolution of 1.3 nm per pixel. The structural information was directly retrieved from the diffraction intensities without prior knowledge and was subsequently confirmed through transmission electron microscopy.